Effects of amino acids and energy intake during late gestation of high-performing gilts and sows on litter and reproductive performance under commercial conditions - Goncalves, M. A. D.; Gourley, K. M.; Dritz, Steven S.; Tokach, Michael D.; Bello, Nora M.; DeRouchey, Joel M.; Woodworth, Jason C.; Goodband, Robert D. (My University, 2016)
The objective of this study was to determine the effects of AA and energy intake during late gestation on piglet birth weight and reproductive performance of high-performing (14.5 total born) gilts and sows housed under commercial conditions. At d 90 of gestation, a total of 1,102 females (PIC 1050) were housed in pens by parity group (gilts or sows) with approximately 63 gilts and 80 sows in each pen, blocked by BW within each pen, and each female was randomly assigned to dietary treatments within BW block. Dietary treatments consisted of combinations of 2 standardized ileal digestible (SID) AA intakes (10.7 or 20.0 g/d SID Lys and other AA met or exceeded the NRC [2012] recommendations) and 2 energy intakes (4.50 or 6.75 Mcal/d intake of NE) in a 2 x 2 factorial arrangement. Data were analyzed using generalized linear mixed models specified to recognize pen as the experimental unit for parity and the individual female as the experimental unit for dietary treatments. Results indicate an overall positive effect of high energy intake on BW gain during late gestation, although this effect was more manifest under conditions of high, as opposed to low, AA intake (interaction, P < 0.001). Furthermore, the magnitude of BW gain response to increased energy intake was greater (P < 0.001) for sows compared with gilts. Sows fed high energy intake had a reduced probability of piglets born alive (P < 0.004) compared with those fed low energy, but no evidence for differences was found in gilts. This can be explained by an increased probability (P = 0.002) of stillborns in sows fed high energy intake vs. sows fed low energy intake. There were no evidences for differences among dietary treatments in litter birth weight and individual piglet birth weight of total piglets born. However, individual born alive birth weight was approximately 30 +/- 8.2 g heavier (P = 0.011) for females fed high, as opposed to low, energy intake. Furthermore, piglets born alive were approximately 97 +/- 9.5 g heavier (P < 0.001) for sows than for gilts. Preweaning mortality was decreased (P = 0.034) for females fed high AA intake compared with females fed low AA intake regardless of energy level. In conclusion, 1) BW gain of gilts and sows depended not only on energy but also on AA intake, 2) sows fed increased amount of energy had an increased stillborn rate, and 3) increased energy intake during late gestation had a positive effect on individual piglet birth weight with no evidence for such an effect for AA intake.
Citation: Goncalves, M. A. D., Gourley, K. M., Dritz, S. S., Tokach, M. D., Bello, N. M., DeRouchey, J. M., . . . Goodband, R. D. (2016). Effects of amino acids and energy intake during late gestation of high-performing gilts and sows on litter and reproductive performance under commercial conditions. Journal of Animal Science, 94(5), 1993-2003. doi:10.2527/jas.2015-0087
Keywords: Amino Acids; Birth Weight; Energy; Gestation; Gilts; Sows